An Experimental Approach for Studying the Fuel Characteristics of Agricultural Waste Based Charcoal A Case Study - Lonia, B.; Bansal, R.K. (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
This paper enlists fuel characteristics of agricultural wastes experimentally.Woody charcoal has been the primary fuel for cooking (power generation) in many countries because it is cheap and easily available .However, using wood charcoal has consequences on health and pollution because of smoking. This study aims at providing agricultural waste as an alternative to woody charcoal using agricultural based wastes (dry leaves, coffee husk, sugarcane trash, grass,etc) converted into charcoal briquettes to provide much needed source of cheap fuel that is cleaner in burning. The agriwaste, like rice-straw, saw-dust, sugarcane-trash, coir-pith, peanut -shells, wheat-stalks and straw, cotton-seed, stalks and husk, soybean stalks, maize stalks and cobs, sorghum, bagasse, waste wood, walnut shells, sunflower seeds, shells, hulls and kernels and coconut husk can be fruitfully utilized in power generation. This stuff is otherwise a waste and liability and consumes a lot of effort on its disposal; in addition to being a source of fire and health hazard. Apart from the above, it causes serious air pollution in the form of smoke, un-burnt suspended particles and unwanted addition of heat to atmosphere. Surely, agriwaste stuff at present is available in abundance and prospects of its utilization in producing energy are enormous. On the basis of calorific value, agri-residue is comparable with low quality coal.Manual extruder machine having a capacity of pressing 30kg/hr and the carbonizer converts 15kg of input agricultural wastes into 5kg of burned charcoal within 25 minutes. Power can be generated from 5 Kw to 10Kw by using 10kg of briquetted agricultural charcoal.